2009
DOI: 10.1111/j.1745-4573.2009.00159.x
|View full text |Cite
|
Sign up to set email alerts
|

QUALITY CHARACTERISTICS OF MEAT FROM WILD RED DEER (CERVUS ELAPHUS L.) HINDS AND STAGS

Abstract: The objective of the present study was to determine the chemical composition as well as physicochemical and sensory properties of meat (musculus longissimus lumborum) from red deer (Cervus elaphus L.) hinds and stags harvested in forests of north‐eastern Poland. Red deer meat was found to have a low fat content and a high content of total protein and water‐soluble nitrogen in relation to total nitrogen. The total collagen content of meat was relatively low. Meat from hinds contained larger amounts of the above… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
2

Year Published

2011
2011
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 58 publications
4
23
2
Order By: Relevance
“…In the present study, the average malondialdehyde (MDA) content of meat from roebucks was comparable to that determined in an experiment performed by Daszkiewicz et al (2009) High TBA values (up to 6 μg of MDA per g of meat) in meat from farm-raised sika deer (Cervus nippon) were recorded by Okabe et al (2002). The increase in TBARS values observed in meat in the first phase of cold storage in the present experiment was probably due to the presence of residual oxygen in the package.…”
Section: Discussionsupporting
confidence: 60%
“…In the present study, the average malondialdehyde (MDA) content of meat from roebucks was comparable to that determined in an experiment performed by Daszkiewicz et al (2009) High TBA values (up to 6 μg of MDA per g of meat) in meat from farm-raised sika deer (Cervus nippon) were recorded by Okabe et al (2002). The increase in TBARS values observed in meat in the first phase of cold storage in the present experiment was probably due to the presence of residual oxygen in the package.…”
Section: Discussionsupporting
confidence: 60%
“…The lack of differences in color between male and female mountain reedbuck, impala and kudu may be due to no differences in the Mb content and physical activity between the males and females in these species (Hoffman et al, 2009b). Similarly, no color differences were observed between male and female roe deer (Daszkiewicz et al, 2009;Purchas et al, 2010;Daszkiewicz et al, 2012). However, differences in meat color have been observed for gemsbok (Oryx gazella), with females having lower L*, b*, hue and chroma values (Hoffman and Laubscher, 2010), which contradicts the hypothesis that males have darker muscle than females.…”
Section: Factors Influencing Color Of Ungulate Meatsmentioning
confidence: 75%
“…In this respect, Hakimov et al (32) showed that estrogen, female sex hormone, reduces types I and III collagen synthesis in porcine muscles. Many researchers have also reported that the meat from male species is tougher than from female species (33)(34)(35).…”
Section: Eff Ects Of Gender On Meat Qualitymentioning
confidence: 99%